P190 A simplified approach for patients with SLE to report disease activity using a revised version of the swedish systemic lupus activity questionnaire. (23rd March 2020) - Pettersson, Susanne; Illescas-Bäckelin, Vera; Jönsen, Andreas; Gunnarsson, Iva; Trysberg, Estelle; Leonard, Dag; Sjöwall, Christopher; Svenungsson, Elisabet
Abstract : Background/Purpose: We compared patients' assessments of SLE disease activity, reported by the SWE-SLAQr, with physicians' assessments using SLE activity measure (SLAM) and SLE disease activity index (SLEDAI-2K). Methods: Patients (n=115), median age 43 (IQR 24) years, disease duration 15 (IQR 17) years filled out SWE-SLAQr prior to physicians' assessments. Correlations (Spearman's ρ) were calculated between SWE-SLAQr-total, sub-scales (Symptom score, Patients global) and physicians SLAM, SLEDAI-2K with and excluding the laboratory items, further corresponding items in SLAQ and SLAM were explored. Results: Correlations between patients' and physicians' assessments were higher for SLAM-nolab: SWE-SLAQr total, ρ=0.69, Symptom score, ρ=0.67, and Patients global, ρ=0.68 than for SLAM: SWE-SLAQr total, ρ=0.51, Symptom score, ρ=0.49, and Patients global, ρ=0.53. The items fatigue (ρ=0.72) and alopecia (ρ=0.71) showed highest degree of correlation, and dyspnea/pleuritic chest pain had the lowest correlation between patients' and physicians' assessments (ρ=0.19, p=0.039). Correlations with SLEDAI-nolab were lower (ρ≤0.36) for all subscales. No correlations were found between patients' and physicians' assessments when using SLEDAI-2K (ρ<0.09 for all). Conclusions: We conclude that SWE-SLAQr performed equally well as SLAQ, demonstrating that the shorter version can be used to monitor disease impact. We encourage further use of SWE-SLAQr and recommend its implementation in clinical care, we believe it is especially well suited to support digital and telephone contacts. However further attention is needed to evaluate the discrepancy between physicians' and patients' evaluation of thoracic pain/symptoms.